Effect of Ultrasound and Freeze‐Drying to Enhance the Extraction of Phenolic Compounds in Dragon Fruit Peels and Apply Them in Edible Starch‐Based Films - Santos, Newton Carlos; Almeida, Raphael Lucas Jacinto; Albuquerque, Juliana Cruz; Lima, Thalis Leandro Bezerra; Sousa, Francisca Moisés; Alcântara Silva, Virgínia Mirtes; Melo, Mylena Olga Pessoa; Filho, Manoel Tolentino Leite; Santos Silva, Rosenildo; Silva Santos Pinheiro, Larissa; Santos Oliveira, Alison; Albuquerque, Aline Pacheco; et al. (Packaging technology & science, 2024)
ABSTRACT In this study, dragon fruit peels were subjected to different times (5, 10, 15, 20 and 25 min) of ultrasound pretreatment (4.870 W m−2/25°C) and then freeze‐drying (FD) (−56°C/48 h) to obtain powder particles, which underwent physical–chemical, functional and structural characterisation. Additionally, the extraction of total phenolic compound (TPC) was evaluated through ultrasound‐assisted kinetics and mechanical agitation. Finally, films based on black rice starch were developed with the addition (0.5, 1.5 and 2.5%) of dragon fruit peel powder particles, and their physical, barrier, antioxidant, structural and mechanical properties were evaluated. The results obtained showed that all particles had low water content (4.21%–6.58%) and high solubility (84.62%–88.73%) with a reduction in particle size (23.21–39.32 μm). In the extraction of TPC, the synergistic effect of the tested conditions increased efficiency, reaching 686.66 mg GAE/100 g for pretreated dragon fruit peel powder particles (25 min) in 180 min of extraction. Furthermore, the type ‘A’ crystallinity structure did not change significantly with pretreatment, but there was a reduction in peak area, reflecting on relative crystallinity, with a maximum decrease of 29.04%. The starch‐based films produced with 2.5% dragon fruit peel powder particles showed low solubility (28.72%) and low water vapour permeability (5.03 × 10−8 g mm s−1 m2 Pa), however, they contained higher levels of TPC (31.78 mg GAE/100 g film) and antioxidant activity (8.17 μmol TE/g film) that were easily migrated in aqueous medium. Furthermore, they also presented low values of tensile strength at break (3.41 MPa) and Young's modulus (4.18 MPa), as well as a high value of elongation at break (45.82%). Finally, our results highlight the potential of ultrasound as a pretreatment for FD of dragon fruit peels, paving the way for the development of rice starch‐based food packaging. This study investigates the effects of ultrasound and freeze‐drying on the extraction of phenolic compounds from dragon fruit peels. The research focuses on applying these extracted compounds in starch‐based edible films to enhance their antioxidant properties. The results show that the combined use of ultrasound and freeze‐drying optimizes the extraction of phenolic compounds, leading to more effective and functional edible films for potential use in food preservation.